2011
DOI: 10.1021/cs200353x
|View full text |Cite
|
Sign up to set email alerts
|

Solid Cocatalysts for Activating Manganese Triazacyclononane Oxidation Catalysts

Abstract: Immobilizing a homogeneous catalyst provides obvious handling benefits, but ideally can also enhance catalyst productivity or selectivity because of beneficial interactions between the surface and the active site. Here, Mn 1,4,7-trimethyl-1,4,7-triazacyclononane dimers (1) are activated by carboxylate-containing solids for cyclooctene epoxidation/dihydroxylation with H2O2 at 0 °C. The productivity (TON, moles per mole 1) and selectivity (to cis-diol) of cyclooctene oxidation by 1 are known to be tuned by choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The recognition that carboxylic acids act as ligands stimulated renewed interest in heterogeneous Mn-TMTACN catalysts first investigated by De Vos and co-workers. 78 In contrast to the early studies in which the complexes were immobilised on mesoporous silica gel via a specifically modified TMTACN derivative, Notestein and co-workers [79][80][81] reported that immobilisation of the catalyst by in situ reduction of [Mn IV,IV 2 -(m-O) 3 (TMTACN) 2 ] 2+ in the presence of carboxylic acid coated silica particles allowed for similar levels of activity to be observed, both for epoxidation and cis-dihydroxylation, as found previously in homogeneous reactions by de Boer et al (vide supra). 69 Although characterisation of species formed in solution is relatively straightforward, when immobilised on surfaces/particles the application of spectroscopic methods becomes more challenging.…”
Section: Trimethyl-triazacyclononane Based Ligands For Manganese Catamentioning
confidence: 99%
“…The recognition that carboxylic acids act as ligands stimulated renewed interest in heterogeneous Mn-TMTACN catalysts first investigated by De Vos and co-workers. 78 In contrast to the early studies in which the complexes were immobilised on mesoporous silica gel via a specifically modified TMTACN derivative, Notestein and co-workers [79][80][81] reported that immobilisation of the catalyst by in situ reduction of [Mn IV,IV 2 -(m-O) 3 (TMTACN) 2 ] 2+ in the presence of carboxylic acid coated silica particles allowed for similar levels of activity to be observed, both for epoxidation and cis-dihydroxylation, as found previously in homogeneous reactions by de Boer et al (vide supra). 69 Although characterisation of species formed in solution is relatively straightforward, when immobilised on surfaces/particles the application of spectroscopic methods becomes more challenging.…”
Section: Trimethyl-triazacyclononane Based Ligands For Manganese Catamentioning
confidence: 99%
“…Non‐Os‐metal catalysts for the AD reactions of trisubstituted alkenes remain underdeveloped. Previous examples of non‐Os‐metal‐catalyzed cis ‐dihydroxylation reactions are either confined to the AD reactions of mono‐ and/or di‐substituted alkenes using chiral Fe or Mn catalysts or belong to non‐enantioselective cis ‐dihydroxylation reactions (with scarce use of trisubstituted alkene substrates) catalyzed by compounds of transition metals such as Ru, Mn, Fe, Mo, and Pd . A recent report demonstrates enantioselective anti ‐dihydroxylation of alkenes (including trisubstituted ones) catalyzed by Mo‐bishydroxamic acid complex .…”
Section: Discussionmentioning
confidence: 99%
“…Silanes were grafted onto silica utilizing a previously reported method (Figure 2). [19][20][21] Silica (Selecto) was dehydrated overnight at 120°C under dynamic vacuum. 1-2 g dehydrated silica was added to 50 mL of anhydrous pyridine in a round bottom flask under N 2 with stirring, and 2-(carbomethoxy)-ethyltriethoxysilane was added at 1.0 mmol of silane per g of silica.…”
Section: Grafting Of Silanesmentioning
confidence: 99%